Template-assisted formation of microsized nanocrystalline CeO2 tubes and their catalytic performance in the carboxylation of methanol - Schneider, Jörg J.; Naumann, Meike; Schäfer, Christian; Brandner, Armin; Hofmann, Heiko J.; Claus, Peter (Beilstein Journal of Nanotechnology, 2011)
Polymethylmethacrylate (PMMA)/ceria composite fibres were synthesized by using a sequential combination of polymer electrospinning, spray-coating with a sol, and a final calcination step to yield microstructured ceria tubes, which are composed of nanocrystalline ceria particles. The PMMA template is removed from the organic/inorganic hybrid material by radio frequency (rf) plasma etching followed by calcination of the ceramic green-body fibres. Microsized ceria (CeO2) tubes, with a diameter of ca. 0.75 µm, composed of nanocrystalline agglomerated ceria particles were thus obtained. The 1-D ceramic ceria material was characterized by X-ray diffraction, scanning electron microscopy (SEM), high-resolution transmission electron microscopy (HRTEM), UV–vis and photoluminescence spectroscopy (PL), as well as thermogravimetric analysis (TGA). Its catalytic performance was studied in the direct carboxylation of methanol with carbon dioxide leading to dimethyl carbonate [(CH3O)2CO, DMC], which is widely employed as a phosgene and dimethyl sulfate substitute, and as well as a fuel additive.
Keywords: activation of CO2; ceria; electrospinning; exotemplating; nanotubes